P 34. High-order body representations affect human body sway. Issue 8 (August 2021) - Schulleri, K.; Michel, Y.; Lee, D.; Johannsen, L.
Abstract : Motivation & Objectives The variance of human body sway can be explained by anthropometric parameters, such as body height and weight, to some extent. However, high-level factors, such as body representations, might additionally influence postural control, as people with distorted body representations, like anorexic and bulimic patients, have shown more body sway in previous literature. Moreover, anthropometry has been seen to have a different relationship with body sway dependent on sex, showing a higher influence on body sway in males than in females. Therefore, the aim of this study is to investigate the relationship between body representations and postural control, and the influence of a participant's gender. We expected body image and body schema accuracy to affect postural control. Furthermore, gender differences were expected to alter the influence of anthropometry and body image on body sway control. Methodology Anthropometric measurements were taken in 44 young adults (26.93 ± 3.63 years) with a Seca scale and a flexible measurement tape. As body image measures Body Image Distortion (BID) and Body Image Dissatisfaction (BIDS) were assessed. Body schema was assessed with both the Hand and Foot Laterality Task (limb-specific motor imagery task) and a whole-body taking-a-posture task. Body sway was assessed in two normal bipedal quiet standing conditions with 6 trials of 35s duration each: 1) Eyes closed and 2) Head in Neck, Eyes closed. To analyze the relationship between body representations and human body sway, a Hierarchical Multiple Linear Regression was calculated with the following levels: 1) stance condition, 2) anthropometry, 3) body image, 4) body schema. Results Due to missing data and multivariate outliers, four subjects were excluded from statistical analysis. Across 40 subjects (20 females, 20 males), adding body image measures increased the explained variance significantly. Furthermore, adding body schema measures also increased the explained variance significantly. Therefore, the final model containing body image and body schema, additionally to stance condition and body height, explained around 45% of body sway. Moreover, gender differences in the relationship between anthropometry, body image, and limb-specific body schema were observed. While in females, body height and foot-specific body schema did not increase explained variance, it did so in males. In contrast, adding body image measures explained variance in females, but not in males. Conclusion High-order body representations, such as body image dissatisfaction, body image distortion, and body schema accuracy, affect the control of human body sway. Furthermore, the influence of anthropometry, body image, and limb-specific body schema on body sway control seems to be altered by gender.